Optimalisasi Bahasa Indonesia dalam Strategi Promosi Kesehatan - Meilina Widya Dali; Renita Patra; Putri Aulia Mokoil; Sri Fadila Lanyahi; Siti Nurhidayah Bito; Dewi Listiani Tino; Naysila Tolinggi; Mutiara Hala; Moh. Putra Vergiawan Yunus; Regita Wahyuni Hipi; Aprilia Banjele; Sri Meylidya Gagowa; Nofia Djau; Lidya Dwi Aurelia; Masdaira Masdaira (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Health promotion is an essential effort to improve public health, and its effectiveness is strongly influenced by the communication strategies employed, particularly the use of language. Indonesian plays a crucial role as a medium for delivering health messages that are clear, accurate, and easily understood by the community. This study aims to examine the role of Indonesian as an effective medium in health promotion activities at community health centers. The research employed a qualitative descriptive approach, with data collected through in-depth interviews with health workers involved in health promotion programs. The findings indicate that the use of simple, communicative, and context-appropriate Indonesian enhances public understanding, awareness, and acceptance of health information. However, several challenges were identified, including differences in language comprehension among community members, especially the elderly, and the risk of miscommunication. Overall, the study concludes that optimizing the use of Indonesian tailored to the characteristics of the target audience can significantly improve the effectiveness of health promotion and encourage positive health behavior changes in the community.